The Influence of Product Innovation, Marketing Strategy, and Perceived Value on Increasing Salted Fish Sales among SMEs in Sei Berombang - Muhammad Fauzi Ritonga; Muhammad Irwansyah Hasibuan; Mhd. Amin (UNIVERSITAS PAKUAN, 2026)
This study aims to analyze the effect of product innovation, marketing strategy, and perceived value on increasing salted fish sales among micro, small, and medium enterprises in Sei Berombang. The research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to salted fish MSME owners and analyzed using multiple linear regression analysis. The analysis included partial tests, simultaneous tests, and coefficient of determination testing. The results of the study indicate that product innovation has a positive and significant effect on sales growth, suggesting that improvements in product quality, variety, and packaging can enhance consumer interest and increase sales performance. Marketing strategy does not have a significant effect on sales growth, indicating that the marketing practices implemented by MSMEs have not yet been effective in driving higher sales, possibly due to limited creativity, low utilization of digital marketing channels, and conventional promotional approaches. In contrast, perceived value has a positive and significant effect on sales growth, demonstrating that consumers’ perceptions of product benefits, price fairness, and overall satisfaction play an important role in influencing purchasing decisions. Simultaneously, product innovation, marketing strategy, and perceived value have a significant effect on increasing sales. The coefficient of determination shows that a substantial proportion of sales growth variation can be explained by these variables. The findings imply that improving sales performance among salted fish MSMEs in Sei Berombang requires an integrated approach that prioritizes continuous product innovation, strengthens perceived value, and enhances marketing strategies to better align with market conditions and consumer preferences.